SOME OBSERVATIONS ON THE SIZE DISTRIBUTION AND THE OCCURRENCE OF GROWTH RINGS IN THE SCALES OF THREE SPECIES OF CYNOGLOSSUS AT CALICUT - Seshappa, G (Indian Journal of Fisheries, 2011)
Observations have been made on the length-frequency trends in three of the less common species of Cynoglossus at Calicut during the years 1969-73, these species being C. bilineatus (Lacepede). C. puncticeps (Richardson) and C. lida (Bleeker). As these species occur only as occasional specimens in the fish catches, large samples were not available for studying the month-to-month variation patterns in the size distribution, and so the annual totals are considered here, and these give some idea of the sizelimits and the prevailing sizes during the different years. 204 individuals of C. bilineatus were measured during the psriod (5-5.9 to BBSS. 9 cm); of C. puncticeps, 316 specimens were measured (5-5.9 to 20-20.9 cm groups); and of C. lida, 138 individuals were measured (14-14.9 cm to 21-21.9 cm). In all the three species, the scales revealed growth rings comparable to those described in the case of the Malabar sole, C. macrostomus (Norman); the trend of occurrence of these growth rings in the three species is described and discussed.